Evaluating the performance of nursing students in the clinical field - Esmaeili, Mehrdad; Toloie Eshlaghy, Abbas; Afshar Kazemi, Mohammadali; Motadel, Mohammadreza (Advances in Nursing & Midwifery, 2021)
Background: Considering the large number of nursing students and the need for their skills training as an internship in the field under the supervision of clinical nurses, performance appraisal plays an essential role. Objectives: the purpose of this study is to determine the current status and evaluate the clinical performance of nursing students in the clinical field. Methods: The present study is a descriptive cross-sectional study. The research sample includes all students of the 7th and 8th semesters of nursing who had internships in the field, of which 145 were and all of them participated in the study with satisfaction. The clinical performance evaluation checklist of Esmaili nursing students and colleagues in 2013 was used. This questionnaire has 28 questions in three areas of nursing process with 12 questions, professionalism with 9 questions and ethical principles with 7 questions. Validity The face and content validity of the instrument and its reliability were obtained by internal correlation with Cronbach’s alpha / 92. SPSS statistical software version 20 was used for data analysis. Descriptive statistics were used to describe the data. Results: The results showed that the mean and standard deviation of the total performance evaluation of 7th and 8th semester nursing students is 2.03 + - .5 which is in the average range. It was related to the scope of the nursing process with 2 + - .5. The mean score of the professional behavior range was 2.1 + - .6. Conclusion: Findings showed that 7th and 8th semester nursing students are moderate in their performance evaluation.